Comparative Study of Liver Function and Rh Blood Group between both Physiological and Pathological Neonatal Jaundice - Ayia N. Kamal; Ali F. Hassan (College of Pharmacy University of Baghdad, 2021)
Abstract Backgrounds: Jaundice occurs in most newborn due to increased bilirubin concentration. Jaundice is observed during the first week after birth in approximately 60% of term neonates. A high level of bilirubin is neurotoxic and may cause neonatal kernicterus, auditory neuropathy or death. Objectives: to compare the Rh group compatibility, serum bilirubin (total and direct), serum albumin and several liver enzymes between physiological and pathological neonatal jaundice Materials and Methods: A cross sectional study for one hundred neonates with jaundice divided into group 1: 50 newborns with physiological jaundice, Group 2: 50 newborns with pathological jaundice. Blood samples taken from each patient use to determination of Rh Group and blood group, serum bilirubin (total and direct, liver enzymes and albumin concentration. Results: in the present study Rh Compatibility show a significant relationship between newborns with physiological and pathological jaundice (p<0.05). Serum bilirubin (total and direct), serum albumin concentration and several liver enzymes were significantly higher when compare newborns with pathological jaundice with newborns of physiological jaundice (p<0.05). Conclusion: these finding demonstrate that newborns with pathological jaundice have higher concentrations of these parameters as compared with physiological jaundice .